Calling for the Study of the Neuroscience of the Sports Fan Consumer - Cayolla, Ricardo (2021)
Sports fans and fandoms are special (and extreme) cases of the consumerbrand relationship concept. The implications for markets may be positive (e.g., purchasing merchandizing), but also negative (e.g., ostracizing rivals’ sponsors). Such behavior calls for a deeper understanding, but traditional market research methods tend to fail to capture the underlying unconscious/emotion dimensions. Here, we explore the pertinent concepts (brands, self-construal, consumer-brand relationships, brand communities and tribes, and fan identity) and suggest the participation of consumer neuroscience to tackle the neural and psychological grounds of fan behavior.